2016
DOI: 10.1002/aenm.201601805
|View full text |Cite
|
Sign up to set email alerts
|

NiFe Alloy Protected Silicon Photoanode for Efficient Water Splitting

Abstract: time-saving, ecofriendly, and controllable, avoiding the expensive and complicated ALD process. [22] The resulting np + -Si/ SiO x /NiFe photoanode exhibited an extremely large photovoltage of 620 mV, and a high solar-to-O 2 efficiency of 3.3%, a low onset potential of 0.89 V versus RHE (Reversible Hydrogen Electrode) for OER, and achieved a light-limited photocurrent density of 30.7 mA cm −2 at 1.23 V versus RHE in 1.0 m KOH electrolyte. To the best of our knowledge, the performance of np + -Si/SiO x /NiFe ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 42 publications
5
123
0
Order By: Relevance
“…[22,[74][75][76][77][78][79][80] The semiconductor materials are loaded on the electrode surface as a thin film to absorb light for the generation of activated electrons and holes. [81] Nevertheless, cells composed of a photoanode/photocathode and a noble-metal-based counter electrode would be more practical, as shown in Figure 2i,j. Water is oxidized on the anode by the photogenerated holes.…”
Section: Photoelectrochemical (Pec) Water Splittingmentioning
confidence: 99%
“…[22,[74][75][76][77][78][79][80] The semiconductor materials are loaded on the electrode surface as a thin film to absorb light for the generation of activated electrons and holes. [81] Nevertheless, cells composed of a photoanode/photocathode and a noble-metal-based counter electrode would be more practical, as shown in Figure 2i,j. Water is oxidized on the anode by the photogenerated holes.…”
Section: Photoelectrochemical (Pec) Water Splittingmentioning
confidence: 99%
“…These Ni 0 atoms could diffuse toward the Si surface, and thus the silicide phase (i.e., NiSi) could be generated following the electroless reduction of Ni cations. [9,18,21] The present results revealed that this photoinduced adaptive layer can significantly increase the band bending near the silicon/metal/electrolyte interface and thereby induce a higher barrier height, thereby leading to the enhancement of photovoltage. Guided by all these findings, we propose that the formation of this adaptive phase concurs with the transformation of nickel metal into nickel oxides/oxyhydroxides and the presence of exposed silicon oxide on the electrolyte/electrode interface, as displayed in the schematic for photoinduced water oxidation on n-Si@Ni (Figure 8a).…”
Section: Resultsmentioning
confidence: 63%
“…Most importantly, we verified that this adaptive phase was formed at the junction between silicon and nickel with a fringe distance of 0.186 nm, corresponding to the (102) lattice plane of orthorhombic NiSi. 2019, 9,1901308 (a Si = 5.468 Å) matches with two orthorhombic NiSi (200) lattices (a NiSi = 3.060 Å). Energy Mater.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations